Os fatores críticos para a sustentabilidade do Lean Manufacturing: revisão sistemática da literatura, estudo de caso e opinião de especialistas - Lopes, Natalia Roberta (Universidade Federal de São Carlos, 2019)
Lean manufacturing continues to be widespread in the business world as a management philosophy to reduce waste. Despite this, the sustainability of the results of lean initiatives has proved difficult to achieve. There is a limitation on the part of organizations in understanding the factors that influence lean sustainability in all organizational environments. In this direction, the objective of the research was to identify the critical factors for manufacturing companies to sustain their Lean initiatives over time. For this the mixed research method was used, combining the systematic review of the literature, case study and expert opinions. In the systematic review, articles were filtered in scientific journals: Scopus, Engineering Village, Proquest and Web of Science in order to identify in the literature the factors mentioned as critical to sustain lean. Thus, combining the review with snowball methods and expert opinion, we obtained a list of 21 factors. This list was analyzed in the case study with two industries for refinement of the list. Finally, the list of factors passed by the analysis of 5 experts, in the end 19 factors were considered as critical. The results achieved contribute to the professionals have a vision of what aspects should be addressed throughout the Lean journey. In the academic context, the contribution was to compile the lean sustainability factors that are spread in the literature and to show which ones should be explored.
Keywords: Fatores; Revisão sistemática da literatura; Estudo de caso; Lean manufacturing; Factors; Systematic review of the literature; Case study; ENGENHARIAS::ENGENHARIA DE PRODUCAO